Fibroblast Growth Factor 22 Inhibits ER Stress-Induced Apoptosis and Improves Recovery of Spinal Cord Injury - Zhu, Sipin; Chen, Mengji; Chen, Min; Ye, Jiahui; Ying, Yibo; Wu, Qiuji; Dou, Haicheng; Bai, Liyunian; Mao, Fangmin; Ni, Wenfei; Yu, Kehe (Frontiers in Pharmacology, 2020)
Currently, to inhibit or reduce the neuronal cell death is the main strategy to improve the recovery of spinal cord injury (SCI). Many therapeutic interventions for SCI using neurotrophic factors have focused on reducing the area damaged by secondary, post-injury degeneration, to promote functional recovery. In this report, we investigated the mechanism of ER stress-induced apoptosis as well as the protective action of fibroblast growth factor 22 (FGF22) in vivo. Our results demonstrated that ER stress-induced apoptosis was involved in the injury of SCI model rats. FGF22 administration improved the recovery and increased the neurons survival in the spinal cord lesions of the model mice. The protective effect of FGF22 is related to the inhibition of CHOP, GRP78 and caspase-12, which are ER stress-induced apoptosis response proteins. Meanwhile, FGF22 administration also increased the survival of neurons and the expression of growth-associated protein 43 (GAP43) which was related to the neural regeneration. We also demonstrated that the protective effect of FGF22 We also demonstrated that the protective effect of FGF22 effectively reduces neuronal apoptosis and promotes axonal regeneration. Our study firstly illustrated the role of FGF22 in the recovery of SCI is related to the inhibition of ER stress-induced cell death via the activation of downstream signals, also suggested a new trend of FGF22 drug development in the central neural system injuries which involved in the chronic ER stress-induced apoptosis.